1988
DOI: 10.2190/1grb-rkbh-nb2a-ppwr
|View full text |Cite
|
Sign up to set email alerts
|

Outcome from Carotid Endarterectomy. Neuropsychological Performances, Depressive Symptoms and Quality of Life: 8-Month Follow-up

Abstract: A preliminary study was carried out on a population of twenty-five consecutive and unselected patients undergoing carotid endarterectomy. A matched control group of subjects suffering from same pathology, but unoperated, was compared to experimental sample. A battery of neuropsychological tests, the Zung Self-Rating Depression Scale and the Jachuck's Quality of Life Impairment Scale were administered one week before surgery, two weeks after (surgical sample only) and then eight months later. The research shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…These are displayed in table 1 [1, 4, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These are displayed in table 1 [1, 4, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31]. …”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [4, 17, 18, 20, 23, 26, 29]performed two post-operative assessments and one performed three [19]. The mean follow-up time of all 26 studies to the last assessment was 22 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Bornstein et al [26], De Leo et al [27], and Greiffenstein et al [28] reported that verbal tasks improved in patients who underwent CEA on the right side, while no significant change was noted in patients who had CEA on the left side. Thus, a definite conclusion regarding the effect of CEA on cognitive function based on the operation side of CEA cannot be made based on these studies.…”
Section: Discussionmentioning
confidence: 99%